Hot Doug's : the book - Sohn, Doug (Midway, an Agate imprint, 2013)
"A celebration of Chicago's landmark restaurant Hot Doug's, with history from owner Doug Sohn, essays and anecdotes from patrons, and appreciations from culinary professionals"--Provided by publisher.